Influence of social capital on small and medium enterprises performance in Wakiso District, Uganda - Henry Stanley Mbowa; Mbabazi Phelix Businge; Paul Ssemaluulu; Marus Eton (Goodwood Publishing, 2023)
Purpose: This study investigates the influence of Social Capital (SC) on the performance of Small and Medium Enterprises (SMEs) in Kitemu Ward, Wakiso District. It aims to identify both internal and external forms of SC and assess their impact on SME performance. Research methodology: A mixed-methods approach was employed, collecting data from 40 participants through interviews and self-administered questionnaires. Quantitative data were analyzed using MS Excel to generate frequencies and graphs, while qualitative responses were transcribed and grouped into subthemes using content value analysis. Results: Internal SC included elements such as friends, trust, personal savings, family, and social links. External SC comprised customers, financial institutions, government entities, and companies. SC was found to positively influence SME performance by expanding the customer base, increasing profits and sales, and boosting creativity and innovation. Conclusion: Social Capital significantly contributes to SME growth and innovation by leveraging internal and external networks. Limitations: Financial constraints limited data collection coverage. A small sample size may affect the generalizability of findings, while time and data collection biases may also impact the results. Contribution: This is the first study on SC and SME performance in Kitemu Ward. Its findings offer valuable insights for policymakers and stakeholders to develop strategies that integrate SC into SME development, thereby enhancing profitability, customer reach, and financial access.